2015
DOI: 10.1007/s11060-015-1967-y
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary metastasis: is there still a place for neurosurgical treatment?

Abstract: Pituitary metastases are uncommon, ranging from 1 to 5 % of all metastases. Between 10 and 30 % of pituitary lesions are symptomatic responsible for diabetes insipidus, visual field defect or cranial nerve palsy. Primary sites are lung or breast in two-thirds of cases. There is no current reference concerning treatment of such lesions. Overall survival is poor and depends on primary site. Although the role of surgery is currently limited, discussion is warranted in several indications for diagnostic or symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 30 publications
0
25
0
1
Order By: Relevance
“…Resection alone, with or without radiotherapy, does not change survival rates (154). The median survival rate after surgical removal of the pituitary tumor is 6 months (155, 156). Review of the literature determined the mean survival post-Pit Met diagnosis was 13.6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Resection alone, with or without radiotherapy, does not change survival rates (154). The median survival rate after surgical removal of the pituitary tumor is 6 months (155, 156). Review of the literature determined the mean survival post-Pit Met diagnosis was 13.6 months.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of the literature concerning 31 patients, Gilard et al observed that only 20% of patients appeared to be symptomatic [12]. As pituitary metastases often present in a disseminated cancer setting, characteristic clinical pituitary signs are usually overwhelmed by symptoms associated with concomitant extra-pituitary metastases [12]. …”
Section: Discussionmentioning
confidence: 99%
“…In the series of Gilard et al, oculomotor palsy occurred in 42% of patients with metastasis as compared to fewer than 5% of patients with pituitary adenomas [12]. …”
Section: Discussionmentioning
confidence: 99%
“…За даними літератури, частота діагностуван-ня вторинних уражень гіпофіза -від 1 до 19% [8,9]. Відзначено, що у разі виявлення за даними нейрові-зуалізації пухлинного утворення в селярній ділянці та за наявності онкологічного анамнезу це утворення в 90% випадків є метастазом [10][11][12][13]. Частота мета-стазів у гіпофіз, які дають симптоматику, становить від 4,5 до 3,0% [13][14][15][16].…”
Section: украинский нейрохирургический журнал 2018;(1):78-83unclassified